Metabolic co-dependence drives the evolutionarily ancient Hydra–Chlorella symbiosis - Hamada, Mayuko; Schröder, Katja; Bathia, Jay; Kürn, Ulrich; Fraune, Sebastian; Khalturina, Mariia; Khalturin, Konstantin; Shinzato, Chuya; Satoh, Nori; Bosch, Thomas CG (eLife, 2018)
Many multicellular organisms rely on symbiotic associations for support of metabolic activity, protection, or energy. Understanding the mechanisms involved in controlling such interactions remains a major challenge. In an unbiased approach we identified key players that control the symbiosis between Hydra viridissima and its photosynthetic symbiont Chlorella sp. A99. We discovered significant up-regulation of Hydra genes encoding a phosphate transporter and glutamine synthetase suggesting regulated nutrition supply between host and symbionts. Interestingly, supplementing the medium with glutamine temporarily supports in vitro growth of the otherwise obligate symbiotic Chlorella, indicating loss of autonomy and dependence on the host. Genome sequencing of Chlorella sp. A99 revealed a large number of amino acid transporters and a degenerated nitrate assimilation pathway, presumably as consequence of the adaptation to the host environment. Our observations portray ancient symbiotic interactions as a codependent partnership in which exchange of nutrients appears to be the primary driving force. All animals host microorganisms; some of which form ‘symbiotic’ relationships with their host that are mutually beneficial. For instance, the human gut shelters tens of thousands of species of bacteria that break down our food for us, and corals, jellyfish or sea anemones can extract energy directly from sunlight thanks to the algae that live inside their cells. Hydra, a small freshwater animal, lives in a symbiotic relationship with algae called Chlorella that it carries inside its cells. Once an independent organism, Chlorella has evolved in such a way that, in nature, it cannot exist without Hydra anymore. In turn, the algae produce sugars to fuel the animal when it cannot get food from the environment. Yet, despite over 30 years of research, it still remains unclear how exactly the relationship between Hydra and Chlorella works, and how it came to be. Understanding how these two organisms live together could help researchers to figure out the general principles that guide symbiotic interactions. Nitrogen is an element that is essential for life, and organisms can extract it from various sources, such as nitrates or the amino acid glutamine. Here, Hamada, Schröder et al. sequenced the entire genome of Chlorella. This revealed that Chlorella has lost someof the genes required to obtain nitrates, and to process them into nitrogen. However, the genetic analysis showed that the algae express genes that allow them to import amino acids. In turn, analysis of the genes expressed by Hydra when it lives in symbiosis with Chlorella showed that the animal turns on genetic information needed to make glutamine. It thus seems that Hydra creates glutamine which Chlorella can import; the algae then process this amino acid to obtain the nitrogen they need. Hamada, Schröder et al. also discovered that if the environment was artificially enriched in glutamine, Chlorella could live on their own outside of Hydra for a while. The results suggest that symbiotic relationships, such as the one between Hydra and Chlorella, were established because the organisms became dependent on each other for essential nutrients. This co-dependency is strengthened if the organisms lose the ability to produce the nutrients on their own. However, this partnership may be altered when the environment changes too much, especially if the balance of nutrients available gets tipped. For example, if seas that are normally poor in nutrients become suddenly rich in these elements, this may disrupt the existence of symbiotic organisms such as corals.